Glomerular filtration rate in children and young adults with haemato‐oncological disease and infection is best described by three‐compartment iohexol model. Issue 1 (2nd September 2021) - Soeorg, Hiie; Noortoots, Aveli; Karu, Maarja; Saks, Kadri; Lass, Jana; Lutsar, Irja; Kõrgvee, Lenne‐Triin
Abstract: Background : Children with cancer and infection may develop glomerular hyperfiltration. With the aim to determine the prevalence of glomerular hyperfiltration in children and young adults with haemato‐oncological disease and infection, we developed population pharmacokinetic model of iohexol. We further aimed to assess the accuracy of estimated glomerular filtration rate (eGFR) equations and single‐ or two‐point measured GFR (mGFR) formulas compared with GFR based on iohexol clearance from our population pharmacokinetic model (iGFR). Procedure : Hospitalised patients (0.5–25 years) with haemato‐oncological disease and infection were included if their eGFR was ≥80 ml/min/1.73 m 2 at the screening visit. Iohexol plasma concentrations were described by population pharmacokinetic model. Bias, precision and accuracy of 23 eGFR equations and 18 mGFR formulas were calculated. Results : Total of 32 iohexol administrations were performed in 28 patients. Median (range) eGFR was 136 ml/min/1.73 m2 (74–234) and age 15.1 years (0.8–26.0). Three‐compartment model with allometric scaling of central, one peripheral compartment and clearance (with power 0.75) to weight fitted the best. Median (range) iGFR was 103 ml/min/1.73 m 2 (68–140). All except one eGFR equation overestimated GFR. Lund–Malmö revised eGFR equation performed the best, followed by Gao equation. Of single‐ or two‐point mGFR formulas, 15 overestimated iGFR. Modified Jacobsson formula at 5.5 hours performed the best, followed by Fleming formula at 3 hours. Conclusions : In children and young adults with haemato‐oncological disease and infection, renal function is best described by iohexol clearance from three‐compartment pharmacokinetic model, while eGFR equations and single‐ and two‐point mGFR formulas overestimate iGFR.